2010
DOI: 10.1248/bpb.33.1054
|View full text |Cite
|
Sign up to set email alerts
|

Donepezil, a Potent Acetylcholinesterase Inhibitor, Induces Caspase-Dependent Apoptosis in Human Promyelocytic Leukemia HL-60 Cells

Abstract: Apoptosis is a process of active cell death characterized by cell surface blebbing, changes in membrane permeability, nuclear DNA condensation, and internucleosomal fragmentation.1) Several apoptotic pathways exist in cells responsive to apoptotic stimuli, and although each pathway is initiated by different mechanisms, they share a common final phase of apoptosis, which involves the activation of executioner caspases and the dismantling of substrates critical for cell survival.2) Classical apoptosis can be ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 35 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…PGC-1α is the master regulator for mitochondrial biogenesis, and NRF-1 is a transcription regulator for nuclear-encoded mitochondrial genes [25]. Given that high concentrations of donepezil could induce apoptosis [26], we confirmed by Alamar Blue assay that mitochondrial biogenesis enhanced by donepezil was not a result of cell toxicity (data not shown). Taken together, these results show that donepezil induces mitochondrial biogenesis and promotes energy status by stimulating key transcription regulators.…”
Section: Resultsmentioning
confidence: 84%
“…PGC-1α is the master regulator for mitochondrial biogenesis, and NRF-1 is a transcription regulator for nuclear-encoded mitochondrial genes [25]. Given that high concentrations of donepezil could induce apoptosis [26], we confirmed by Alamar Blue assay that mitochondrial biogenesis enhanced by donepezil was not a result of cell toxicity (data not shown). Taken together, these results show that donepezil induces mitochondrial biogenesis and promotes energy status by stimulating key transcription regulators.…”
Section: Resultsmentioning
confidence: 84%
“…Notably, a number of AChE inhibitors are currently used or are under investigation for their potential application in cancer treatment. For instance, donepezil has been reported to induce apoptosis of HL-60 human promyelocytic leukemia cells (31). Galantamine has also been proven to produce anti-proliferation effects against 3T3 cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…The cancer-sensitizing ability of DON and SID, which are aging-related repositioned drugs for Alzheimer's or erectile dysfunction, have been demonstrated in various cancer models (25)(26)(27)(28)(29), suggesting that they have potential as chemotherapeutic agents. In this study, DON and SID were found to sensitize P-gp-overexpressing anti-mitotic drug-resistant cancer cells.…”
Section: Discussionmentioning
confidence: 99%